The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/cxo.12862
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal changes in human myopia: insights from optical coherence tomography imaging

Abstract: The choroid is a vascular tissue which plays a range of critical roles in the normal physiology of the eye, such as supplying the outer retina with oxygen and nutrients and the regulation of intraocular pressure. There is also substantial evidence, particularly from animal studies, that the choroid plays an important role in the regulation of eye growth and the development of common refractive errors like myopia. In recent years, advances in optical coherence tomography technology have improved our ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
93
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 149 publications
(300 reference statements)
5
93
0
Order By: Relevance
“…It is nowadays evident that myopia is strongly correlated with the axial length of the eye and not with its refractive power [18]. The growth of the eye globe is a complex event, which appears to be regulated by signals coming from the retina and the choroid, independent from the brain [19,20]. Some described chemical mediators of this signaling mechanisms are dopamine [21], TGFβ [22], and melatonin [23].…”
Section: Discussionmentioning
confidence: 99%
“…It is nowadays evident that myopia is strongly correlated with the axial length of the eye and not with its refractive power [18]. The growth of the eye globe is a complex event, which appears to be regulated by signals coming from the retina and the choroid, independent from the brain [19,20]. Some described chemical mediators of this signaling mechanisms are dopamine [21], TGFβ [22], and melatonin [23].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that exposure of the retina to a regionally distinct, rather than a spatially uniform, pattern of myopic defocus may provide additional cues to the eye that result in an increased response of the choroid to myopic defocus. An increase in choroidal thickness is thought to contribute to the long‐term slowing of ocular growth . Therefore, the greater thickening of the macular choroid in response to a regionally distinct, rather than spatially uniform imposed myopic defocus, may also provide a potential mechanism explaining the greater efficacy of bifocal and multifocal spectacle lenses, multifocal soft contact lenses and orthokeratology compared to the symmetrical defocus of bilateral myopic under‐correction in slowing the progression of myopia.…”
Section: Discussionmentioning
confidence: 99%
“…Research with animal models suggests that eye growth is influenced by retinal image defocus, with the choroid playing a significant role in mediating the effects of defocus on ocular growth and the development of refractive errors . Studies in a range of species show that a thinning or thickening of the choroid in response to hyperopic or myopic defocus results in a rapid movement of the retina towards the defocused image plane, followed by alterations in scleral growth that eventuates in the development of experimental myopia or hyperopia, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…Experimental settings in both animals [9][10][11][12] and humans [8] show a modulation of choroidal thickness in response to visual inputs which also leads to choroidal secretion of scleral growth regulators [13]. Consequently, the choroid is believed to play an active part in eye growth regulation [14,15]. Eyes that develop myopia both experience a thinning of the choroid and an elongation of the eyeball [16,17] and a study following 101 Australian children over an 18 month period found an association between choroidal thinning and increasing axial length growth [18].…”
Section: Introductionmentioning
confidence: 99%